Work stress, anxiety, depression, and quality of life among nurses in East Java: a cross-sectional study - Susanto, Tantut; Keliat , Budi Anna; Windarwati , Heni Dwi; Nihayati, Hanik Endang; Ati, Niken Asih Laras; Istifada, Rizkiyani; Rokhmah, Dewi; Khoiron, Khoiron (Universitas Airlangga, 2025)
Introduction: Work stress is a significant issue in the nursing profession, often linked to adverse mental health outcomes such as anxiety, depression, and decreased quality of life. This study aimed to investigate the relationships between anxiety, depression, quality of life, and work stress among nurses in East Java Province, Indonesia. Methods: A descriptive cross-sectional design was employed, involving 205 nurses from three cities in Indonesia. Data were collected using standardized instruments: Generalized Anxiety Disorder-7 (GAD-7) for anxiety, the Center for Epidemiologic Studies Depression Scale (CES-D) for depression, World Health Organization Quality of Life-BREF (WHOQOL-BREF) for quality of life, and the Work Stress Scale (WSS) for work stress. Correlation and multiple regression analyses were used to examine the relationships between the variables. Results: The finding revealed significant correlations between work stress, anxiety (p-value 0.001), and quality of life (p-value 0.001). Higher levels of work stress were associated with increased anxiety and lower quality of life scores. However, no significant association was found between work stress and depression in the regression analysis (p-value 0.101). Anxiety and quality of life were significant predictors of work stress, accounting for 13.4% of the variance. Conclusion: This study's findings support targeted interventions that can reduce anxiety and improve nurses' quality of life. These include mental health workplace programs and hospital organizational changes to foster a positive work culture. Given the limitations of self-reported data, future research should incorporate longitudinal designs and objective measures to understand these relationships better.